MUTUALISM IN LESSON STUDY - Patang, Hafira (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
Lesson study has commonly three stages in the implementation. They are plan, do, and see. In the process, a relationship occurs between people who are involved in it. They are the teachers, students, and observers. This research focuses about the positive relation happened between teachers and observers. Positive relation between people who are involved in learning process could improve classroom quality. The positive relation is named âmutualismâ. In biological term, mutualism is when two organisms of different species